Immunomodulatory Effects of Cermai Leaves (Phyllanthus acidus (L.) Skeels) Ethanol Extract on Normal Male Rats and Cyclophosphamide Induction - Nurfadhilah, Dhea; Yuandani, Yuandani; Hasibuan, Poppy Anjelisa Zaitun (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Ethanol extract of Phyllanthus acidus (L.) Skeels leaf contains flavonoids and saponins that were widely used as herbal medicinal plant. The present study focused on exploring the biological potential as well as immunomodulatory effects. AIM: The present study aimed to investigate the immunomodulatory effects of P. acidus extract on total and differential leukocyte count, antibody titer, delayed-type hypersensitivity (DTH) response in normal male rats, and immunosuppressed male rats. METHODS: P. acidus extract was obtained by maceration technique by using ethanol as a solvent. Standardization of P. acidus and phytochemical screening includes examination of alkaloids, flavonoids, glycosides, saponins, tannins, and steroids/triterpenoids. The trial animals were male rats which were divided into two large groups, namely normal group and immunosuppressed group. All animals were given extract on the 1st day until day 14, on 4th day the animals were infected with 2% sheep red blood cells. Immunosuppressed rats were injected by 70 mg/kg bw cyclophosphamide on 8th and 13th day. The immunomodulatory effect was analyzed by evaluating total leukocytes, leukocyte differential, antibody titer, and DTH. RESULTS: Phytochemicals screenings were showed alkaloids, flavonoids, glycosides, saponins, tannins, and steroids/triterpenoids from P. acidus extract. P. acidus extract showed an immunomodulatory activity on normal male rats and immunosuppressed male rats. The result was shown from the increasing of total leukocyte count and leukocyte differential, antibody titer value, and the volume of rat paws were higher than negative control (p < 0.05). CONCLUSION: The results indicated that the P. acidus extract had immunomodulatory effects and its potential to be developed as immunomodulator agent.